Strategic Environmental Assessment of the Kenya Forests Act 2005 - World Bank (Washington, DC, 2013)
Forest in Kenya is an important source of livelihood, environmental services, and economic growth. In November of 2005 the Government of Kenya (GOK) ratified a new Forests Act. The act contains many innovative provisions to correct previous shortcomings, including a strong emphasis on partnerships, the engagement of local communities, and promotion of private investment. The purpose of the Strategic Environmental Assessment (SEA) is to inform, influence, and strengthen the processes of implementing the new Forests Act and inform policy discussions regarding sustainable use forests resources for national development. The SEA examined current risks confronting both woodland and forest environments and the social well-being of communities relying on these resources. Evidence gathered through research and extensive consultation with stakeholders was used to identify the scope for improving institutional structures and governance processes under the planned forestry reforms, notably those relating to the Kenya forest service and the participation of communities and the private sector in forest management. The SEA recommends ways of enhancing the opportunities for environmental and social gain that already form part of the overall goal of the Forests Act.